Factors Influencing Adoption of Internet Banking in Kathmandu Valley - Sigdel, Medhabi (Nepalese Journal of Business, 2024)
This study examines the factors influencing adoption of internet banking in Kathmandu Valley. Internet banking is selected as the dependent variable. Similarly, trust, convenience, reliability, ease of use, security and time saving are selected as the independent variables. The primary source of data is used to assess the opinions of the respondents regarding the factors influencing adoption of internet banking in Kathmandu valley. This study is based on primary data with 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing adoption of internet banking in Kathmandu Valley. The study revealed that trust has a positive impact on adoption of internet banking. It means that increase in trust leads to increase adoption of internet banking. Similarly, time saving has a positive impact on adoption of internet banking. It indicates that increment of time saving leads to increase in adoption of internet banking. Moreover, this study showed security has a positive impact on adoption of internet banking. It means that high security leads to increase in adoption of internet banking. Likewise, reliability has a positive impact on adoption of internet banking. It shows that higher the reliability, higher would be the adoption of internet banking. Similarly, ease of use has a positive impact on adoption of internet banking. It shows that increment in ease of use leads to increase in adoption of internet banking. On the other hand, convenience has a positive impact on adoption of internet banking. It means that higher the convenience, higher will be the adoption of internet banking.